2014
DOI: 10.3413/nukmed-0572-13-03
|View full text |Cite
|
Sign up to set email alerts
|

Early dynamic 18F-FDG PET/CT to diagnose chronic osteomyelitis following lower extremity fractures

Abstract: This pilot study suggests that edFDG-PET may offer a less time consuming add on to standard FDG-PET/CT while being equally accurate. The results should be validated prospectively in larger trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…In line with the non-quantitative studies mentioned in the introduction, i.e. [4, 5, 7, 9, 10], we found increased blood perfusion in the OM lesions (Table 3), as well as in the ST lesions (Table 4). However, as hypothesized, we found a quite clear distinction between the OM lesions and the ST lesions as the increase was significantly higher in the infected soft tissues than in the osteomyelitic lesions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with the non-quantitative studies mentioned in the introduction, i.e. [4, 5, 7, 9, 10], we found increased blood perfusion in the OM lesions (Table 3), as well as in the ST lesions (Table 4). However, as hypothesized, we found a quite clear distinction between the OM lesions and the ST lesions as the increase was significantly higher in the infected soft tissues than in the osteomyelitic lesions.…”
Section: Discussionsupporting
confidence: 91%
“…The study did not report quantitative perfusion, though, but found PET/CT valuable as a tool in the assessment. Two recent papers describe experiences with dynamic PET/CT, using [ 18 F]NaF [9] or [ 18 F]FDG [10] as tracer; both studies reported increased standardized uptake values (SUV) in the volume of interest (VOI) positioned at the site of chronic OM infection.…”
Section: Introductionmentioning
confidence: 99%
“…This technique is similar to performing early whole-body softtissue imaging with 99m Tc-labeled diphosphonate bone scanning using a sweep protocol as a screening tool for sites of joint inflammation. The proposed technique is analogous to prior published work on 2-phase or 3-phase 18 F-FDG PET for chronic osteomyelitis (6). 18 F-FDG PET for imaging of osteomyelitis has been found to have excellent sensitivity and specificity for bone infection, with possibly even higher accuracy than the cur- rent gold standard radionuclide technique of 99m Tc-hexamethylpropyleneamine oxime-or 111 In-labeled white blood cell scintigraphy (7,8).…”
Section: Replymentioning
confidence: 81%
“…More recently, early dynamic PET/CT using [ 18 F]NaF or [ 18 F]FDG has been tested in chronic osteomyelitis suggesting that data on the early radiotracer distribution may provide additional information than standard acquisition however results to be validated prospectively in larger trials [38,39].…”
Section: Bone Infections 211 Peripheral Bone Osteomyelitismentioning
confidence: 99%
“…Preliminary results with 99m Tc-ubiquicidin [29][30][31][32][33][34][35][36][37][38][39][40][41] have been reported in patients with suspected SD. The sensitivity and specificity for detecting SD were 100% and 87%, respectively with a positive predictive value of 95% and a negative predictive value of 100%.…”
Section: Spondylodiscitismentioning
confidence: 99%